Metabolic effects of successful intraportal islet transplantation in insulin-dependent diabetes mellitus. - Luzi, L (1996)
The intraportal injection of human pancreatic islets has been indicated as a possible alternative to the pancreas transplant in insulin-dependent diabetic patients. Aim of the present work was to study the effect of intraportal injection of purified human islets on: (a) the basal hepatic glucose production; (b) the whole body glucose homeostasis and insulin action; and (c) the regulation of insulin secretion in insulin-dependent diabetes mellitus patients bearing a kidney transplant. 15 recipients of purified islets from cadaver donors (intraportal injection) were studied by means of the infusion of labeled glucose to quantify the hepatic glucose production. Islet transplanted patients were subdivided in two groups based on graft function and underwent: (a) a 120-min euglycemic insulin infusion (1 mU/kg/min) to assess insulin action; (b) a 120-min glucose infusion (+75 mg/di) to study the pattern of insulin secretion. Seven patients with chronic uveitis on the same immunosuppressive therapy as grafted patients, twelve healthy volunteers, and seven insulin-dependent diabetic patients with combined pancreas and kidney transplantation were also studied as control groups. Islet transplanted patients have: (a) a higher basal hepatic glucose production (HGP: 5.1 +/- 1.4 mg/kg/ min; P < 0.05 with respect to all other groups) if without graft function, and a normal HGP (2.4 +/- 0.2 mg/kg/min) with a functioning graft; (b) a defective tissue glucose disposal (3.9 +/- 0.5 mg/kg/min in patients without islet function and 5.3 +/- 0.4 mg/kg/min in patients with islet function) with respect to normals (P < 0.01 for both comparisons); (c) a blunted first phase insulin peak and a similar second phase secretion with respect to controls. In conclusion, in spite of the persistence of an abnormal pattern of insulin secretion, successful intraportal islet graft normalizes the basal HGP and improves total tissue glucose disposal in insulin-dependent diabetes mellitus.